360° domain walls: stability, magnetic field and electric current effects. (17th May 2016) - Zhang, Jinshuo; Siddiqui, Saima A; Ho, Pin; Currivan-Incorvia, Jean Anne; Tryputen, Larysa; Lage, Enno; Bono, David C; Baldo, Marc A; Ross, Caroline A
Abstract: The formation of 360° magnetic domain walls (360DWs) in Co and Ni80 Fe20 thin film wires was demonstrated experimentally for different wire widths, by successively injecting two 180° domain walls (180DWs) into the wire. For narrow wires (≤50 nm wide for Co), edge roughness prevented the combination of the 180DWs into a 360DW, and for wide wires (200 nm for Co) the 360DW was unstable and annihilated spontaneously, but over an intermediate range of wire widths, reproducible 360DW formation occurred. The annihilation and dissociation of 360DWs was demonstrated by applying a magnetic field parallel to the wire, showing that annihilation fields were several times higher than dissociation fields in agreement with micromagnetic modeling. The annihilation of a 360DW by current pulsing was demonstrated.